Educational Leadership in Improving the Quality of School-Based Education - Sri Nurabdiah Pratiwi (International Journal of Educational Narratives, 2024)
Background. Quality education is inseparable from how leaders can empower all elements in schools by school conditions. Improving the quality of school-based education, starting from the state of schools that are believed to have weaknesses, is time for improvements. Purpose. Therefore educational leaders must be observant in seeing which conditions are most important for improvement or change so that the goal of improving the quality of school-based education achieves its goals. Making changes in the context of improving the quality of education cannot be done alone but requires the full support of all elements of the school, starting from educators, education staff, students and the school community. Method. This article uses the literature review method by analyzing several research results and some literature related to educational leadership and school-based quality. The literature review method collects data using various literature, such as books, journals, and other references that are considered appropriate to the research topic Results. Effective educational leadership can cover all aspects of schools' need to improve quality, especially the quality of teaching staff as the frontline. The qualified teaching staff is a benchmark for school progress which will eventually become the quality of education. Therefore, it needs to be empowered according to the expertise possessed so that the quality of teaching staff can be improved sustainably. Educational leadership in carrying out their duties must be distinct from their leadership style, which also affects the quality of education. Conclusion. In addition, educational leadership also has competencies that are part of the leader's self to realize the achievement of educational goals.